2006
DOI: 10.1038/sj.jid.5700069
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the CXCL12/CXCR4 Pathway in the Recovery of Skin Following Burns

Abstract: Burn wound healing is a complex process consisting of an inflammatory phase, the formation of granulation tissue, and remodeling. The role of the CXCL12/CXCR4 pathway in the recovery of skin following burns is unknown. We found that CXCL12 is similarly expressed in human, swine, and rat skin by pericyte and endothelial cells, fibrous sheet, fibroblasts, and axons. Following burns, the levels of CXCL12 were markedly increased in human burn blister fluids. One day after injury, there was a gradual increase in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
107
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(116 citation statements)
references
References 32 publications
4
107
0
1
Order By: Relevance
“…In our study, we have used fibroblasts as a general source of CXCL12. However, it should be noted that other dermis-derived cells also secrete CXCL12 [21][22][23][24][25] and therefore our findings may not be restricted to just fibroblasts, but may involve dermisderived stromal cells in general. We propose that dermis-derived cells play a role in creating a directional chemotactic gradient between the epidermis and the dermis, by secreting chemokines in response to epidermis-derived cytokines (e.g.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In our study, we have used fibroblasts as a general source of CXCL12. However, it should be noted that other dermis-derived cells also secrete CXCL12 [21][22][23][24][25] and therefore our findings may not be restricted to just fibroblasts, but may involve dermisderived stromal cells in general. We propose that dermis-derived cells play a role in creating a directional chemotactic gradient between the epidermis and the dermis, by secreting chemokines in response to epidermis-derived cytokines (e.g.…”
Section: Discussionmentioning
confidence: 90%
“…Fibroblasts are known to secrete many chemokines. Recently, it was shown that the constitutive chemokine CXCL12 is also secreted by fibroblasts and its secretion is enhanced upon exposure to stress factors, such as hypoxia, irradiation, and burns [21][22][23][24][25]. CXCL12 secretion is not restricted to fibroblasts though, since endothelial cells and DC are also located in the dermis and also secrete CXCL12 [23,26,27].…”
mentioning
confidence: 99%
“…The fibroblasts applied in our current study express low but measurable levels of surface CXCR4 and CD74. While no information is yet available about the role of the MIF/ CXCR4 axis in fibroblast migration and wound healing, CXCR4 in conjunction with its cognate ligand SDF-1 (CXCL12) have been implicated in fibroblast migration, both through chemotaxis and chemokinesis, as well as in dermal wound healing responses [39,40]. GPCR-mediated cell migratory responses lead to a rise in intracellular calcium as part of the signalling process and MIF-triggered leukocyte migration involves calcium signalling [11].…”
Section: Discussionmentioning
confidence: 99%
“…3-Amino-9-ethylcarbazole was used for color development and sections were counterstained with hematoxylin. As negative controls, sections were stained either with no primary Ab (PBS) or with an isotype-matched control Ab (24,25).…”
Section: Immunohistochemistrymentioning
confidence: 99%